Postcard from Theodor Curtius to Georg Bredig - Curtius, Theodor (1911)
Postcard from Theodor Curtius (1857-1928) to Georg Bredig (1868-1944). The postcard features a black and white image of Curtius sitting next to an open window. Throughout his career, Curtius was a professor of chemistry at the University of Heidelberg, the director of the analytical chemistry department at the University of Erlangen, and a chair of chemistry at the University of Kiel. He published the Curtius rearrangement in 1890 and also discovered diazoacetic acid, hydrazine, and hydrazoic acid.
Keywords: Bredig, Georg, 1868-1944; Curtius, Theodor, 1857-1928; Chemists